3xy+9xy-5xy=

Simple and best practice solution for 3xy+9xy-5xy= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3xy+9xy-5xy= equation:


Simplifying
3xy + 9xy + -5xy = 0

Combine like terms: 3xy + 9xy = 12xy
12xy + -5xy = 0

Combine like terms: 12xy + -5xy = 7xy
7xy = 0

Solving
7xy = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '7'.
xy = 0

Simplifying
xy = 0

The solution to this equation could not be determined.

See similar equations:

| 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 | | 900t-10t^2=0 | | 4(5-4x)-3x=96 | | 2(5-2x)=1.2(3x-5) | | 4(5-4x)-3x=97 | | -6(3x+4)=30 | | 2u-9=-7u | | Tan63=X/4 | | 10x-93=-x+94 | | 3+.05(4a+8)=9-2a | | F(x)=12x-2y | | 20=k/2 | | h=900(t)-10(t^2) | | 4(3x+5)=6(2x+5)-10 | | 1/5(20a)=4–a |

Equations solver categories